Public Opinion on Facebook Rebrand to Meta: A Twitter Big Data Analysis on the First 24 Hours After Meta Launched - Rayan Afif; Moch. Fuad Nasvian (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2022)
This study examines public opinion on the rebranding of Facebook Inc., a parent companyof Instagram, Whatsapp, Oculus, and the main product Facebook itself into Meta. Metawas once a social media company which on October 28th 2021 states that they’re goingto change the focus into also building the Metaverse. For this research outline, researcherswill use three levels of analysis as follows: 1) Sentiment & Behavioral Data Analysis, 2)Public Emotion Detection, 3) Content analysis to study the public sentiment during the dayof the launch of Meta. Researchers analyze tweets out of 10000 data from twitter which isobtained through the MAXQDA software and Python programming language. With thementioned analysis method, this research concluded that the response from twitter users'big data cannot be defined as a success in targeting positive responses. At the firstimpression Meta could not win the users heart where still most of the sentiment aredominated by neutral and negative than the positive response.